Agreement strategies among Malaysian Chinese speakers of English - Azlina Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research aims to discover the agreement strategies adopted by Malaysian Chinese speakers of English in an academic discussion. Using Brown and Levinson’s (1987) Politeness Principle and Speech Acts as frameworks, it seeks to find out the reasons governing their choice of agreement strategies. Student discussions were recorded, transcribed and analysed. Review sessions were also carried out to gain insight into the speakers’ choice of strategies. Analysis of the data revealed five agreement strategies employed by the students during a discussion. During the discussions, the students expressed the speech act of agreement, which support the hearer’s positive face, by directly agreeing with the previous speaker, building upon the previous speaker’s turn, completing and repeating part of the previous speaker’s utterance and giving positive feedback. Of all the strategies, the most often employed and is sustained throughout the discussions is positive feedback. This is followed by building upon utterances, completion of the previous speaker’s utterance and direct agreement. Apart from the Chinese cultural values which may influence the group’s agreement strategies, the findings also reveal that gender has an influence in the participants’ choice of agreement strategies since four out of the five strategies are mainly employed by the female participants. In sum, Malaysian Chinese speakers of English have their own communicative style when expressing agreement acts which is influenced by their cultural values and gender.